Two new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from South India - Anbalagan, Sankarappan; Vijayan, Suruliyandi; Balachandran, Chellapandian; Thiyonila, Berchmans; Surya, Aathmanathan (Zootaxa, 2020)
Two new black fly species, Simulium (Gomphostilbia) dinakarani sp. nov. and Simulium (Gomphostilbia) krishnani sp. nov. are described based on reared adult, pupal and larval specimens collected from the Western Ghats of India. These two new species are placed in the Simulium batoense species-group of the subgenus Gomphostilbia Enderlein. The morphological characters of two new species are compared with other related species of batoense species-group in India. The COI gene has successfully differentiated these two new species from its allies, S. (G.) panagudiense and S. (G.) takaokai of the batoense species group and the phylogenetic analysis by using COI gene sequences supporting its morphological classification.